2020
DOI: 10.3389/fpsyg.2020.00994
|View full text |Cite
|
Sign up to set email alerts
|

Job-Related and Nonjob-Related Gossips Among Low-Ranked Employees in Unionized Service Organization

Abstract: Workplace incivility is a common phenomenon that is frequently found across all organizations and cultures. This study was planned to investigate the impact of workplace incivility on job and non-job related gossips through the mediating role of cynicism and psychological contract violation. The perspective of low-ranked unionized employees was explored through a survey method by using stratified sampling in eight strata, which were formulated based on geographical distribution. A total of four hundred questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 93 publications
1
27
0
Order By: Relevance
“…Table 2 (Fornell-Larcker criteria) and Table 3 (HTMT ratios) in this regard illustrate discriminant value. The first criteria in this regard indicate that the square root of the AVE of variables is higher than the correlations among them ( Hair et al, 2011 ; Bashir et al, 2020 ) as indicated by values in bold and underlined values reported in diagonals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 (Fornell-Larcker criteria) and Table 3 (HTMT ratios) in this regard illustrate discriminant value. The first criteria in this regard indicate that the square root of the AVE of variables is higher than the correlations among them ( Hair et al, 2011 ; Bashir et al, 2020 ) as indicated by values in bold and underlined values reported in diagonals.…”
Section: Resultsmentioning
confidence: 99%
“…Here, it has been observed that predictors along with the green concept are explaining 45% variation in the EBBE, indicating a good level of variance. While three dimensions of design perception were explaining 21% of perception in the green concept (mediating variable) thus predicting a good and reasonable model fitness ( Bashir et al, 2020 ), and a satisfactory level ( Hair et al, 2017 ). In this study, we have also assessed the predictive relevance of the model through Q 2 ( Geisser, 1975 ), and it has been observed that the value of Q 2 was higher than zero, which indicates a good model predictive relevance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, for this purpose, Smart PLS was used for data analysis for several reasons; first, it deals very well with the small sample sizes. Second, it eradicates the issue of normality due to the sample bootstrapping technique (Khalid et al, 2018 ; Bashir et al, 2020 ; Mohsin et al, 2020 ; Naseem et al, 2021 ). For this purpose, construct reliability, discriminant validity, and convergent validity tests were used.…”
Section: Resultsmentioning
confidence: 99%
“…Although workplace incivility has been investigated in depth by researchers in the past ( Saqib et al, 2017 ; Sarwar et al, 2019 ; Bashir et al, 2020 ) and it is a well-documented phenomenon, there is still need to investigate it in public sector organization. Previous research has demonstrated how workplace incivility contributes to knowledge hiding behaviors ( Connelly et al, 2012 ; Peng, 2013 ); however, there seems a missing link that how in academic institutes employees tend to cope with workplace incivility by showing discretionary behaviors in the shape of knowledge hiding ( Srivastava et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%